Information Support Model for the Children’s Leisure and Tourism Industry within the Annual Planning Cycle - FEDYUNIN, Dmitry Valerievich; BEZPALOV, Valery Vasilyevich; LOCHAN, Sergey Alexandrovich; GOLOVINA, Vera Viktorovna; IVANOV, Andrey Viktorovich (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018, 2019)
In the contemporary world, tourism is one of the most profitable and fast-growing sectors of the economy, being a stabilizer of a state’s social economic development, providing an inflow of foreign currencies, improving foreign trade and influencing the development of related sectors. The establishment of a stable tourist services market helps resolve the problem of unemployment and social support of the poor. The study’s purpose is to review seasonality factors related to the creation of a positive image of the children’s leisure and tourism system in the Russian Federation. During the study, the authors applied the systematic approach, strategic approach, analytical approach, methods of comparison and analogy, expert estimates of media monitoring and qualitative methods of text analysis. Main results relate to the theoretical substantiation and the development of methodical recommendations on information media support of the children’s leisure and tourism system. The substantiation of novelty is as follows: the authors found factors of overcoming the lack of a systematic approach and chaotic nature of information media events aimed at supporting the children’s leisure and tourism system. As a result, measures to improve the efficiency of information media support of the events conducted by children’s leisure and tourism organizers depend on the competence and qualification of employees who are in charge of children’s entertainment.